Factors that contribute in employee’s confidence towards incentives safety performance among Petronas employees / Nursyafiqah Tazali - Tazali, Nursyafiqah (Faculty of Business and Management, 2018)
This chapter is intended to provide an overview of the overall study. In this first part of introduction section, an outline of the background and purpose of the study are stated to provide a clear direction of this research. Second, a brief background of the study is presented. Third, a discussion of problem statement of why these research is conducted. Thus, is followed by research question and research objectives, scope of the study, significance of study, limitations of study and this chapter ends with definition of terms.